(untitled) (GnosisWisdom, 2023)
The objective of the study was to determine the degree of relationship between the use of acquisition, coding, recovery and support learning strategies and the academic performance of the Research and Practice Sub-areas in 153 students of the VII cycle of the various specialties of a public pedagogical higher education institution of Peru. Distributed into strata, the learning strategies that most applied in their training were identified among the students. At the same time, information was collected on their Academic Performance in Research and Practice, considering the final evaluation minutes of the academic cycle. For statistical analysis, Pearson’s correlation coefficient was used. The results were: The study established that there is a linear relationship between the use of these learning strategies and academic performance. That there is a greater proportion of use of the coding learning strategy, in relation to the other strategies mentioned. Furthermore, the levels of academic performance in the Research and Practice Subareas showed that on average the results obtained in Practice are higher than those obtained in Research, in addition to obtaining less dispersion in academic performance in Practice. Concluding that the correlations between the learning strategies of acquisition, support and encoding with academic performance in the research area are highly significant, given that their Pearson correlation coefficients are ** 0.193, **0.237 and **0.105 respectively, when p<0.01. The other correlations of remedial learning strategies and total ACRA with academic performance in the Research area are significant since their Pearson correlation coefficient is *0.193 and *0.203 respectively when p< 0.05. While the correlations of the Coding, Retrieval and Support learning strategies are highly significant with the academic performance of the Practice area since the Pearson correlation coefficient is **0.263, **0.223 and **0.208 respectively.